2013
DOI: 10.1007/s00464-013-2792-z
|View full text |Cite
|
Sign up to set email alerts
|

No differences in short-term morbidity and mortality after robot-assisted laparoscopic versus laparoscopic resection for colonic cancer: a case–control study of 263 patients

Abstract: We found RC to be a safe and feasible alternative to LC for colonic cancer. We found that for RC surgical time was shorter and overall procedure time was comparable to that for LC; however, these results should be confirmed in future randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 23 publications
2
60
1
Order By: Relevance
“…In general, most studies [25e30] reported a longer operating time in RC group than in LC group, which is mainly caused by the time taken to dock the robot. Helvind [32] have reported longer setup time for RC (77.1 versus 69.7 min, P ¼ 0.000), but shorter surgical time for RC (165.8 versus 183.4 min, P ¼ 0.006), and there was no difference in the overall procedure time (254.0 versus 243.6 min, P ¼ 0.086). Operating time may also depend on the experience, skill of the surgeon, and technique used, whether fully robotic or the hybrid technique.…”
Section: Discussionmentioning
confidence: 87%
“…In general, most studies [25e30] reported a longer operating time in RC group than in LC group, which is mainly caused by the time taken to dock the robot. Helvind [32] have reported longer setup time for RC (77.1 versus 69.7 min, P ¼ 0.000), but shorter surgical time for RC (165.8 versus 183.4 min, P ¼ 0.006), and there was no difference in the overall procedure time (254.0 versus 243.6 min, P ¼ 0.086). Operating time may also depend on the experience, skill of the surgeon, and technique used, whether fully robotic or the hybrid technique.…”
Section: Discussionmentioning
confidence: 87%
“…One study, a retrospective case control study of 263 patients who underwent either robotic or laparoscopic curative surgery for colonic cancer, found no difference in overall duration, because although the set-up time was significantly longer, this was balanced out by a significantly shorter operative time (Helvind et al 2013). The authors of this study argue that the shorter operative time is due to the technical advantages the robot provides to the surgeon.…”
Section: How Does Robotic Surgery Become Embedded Into Routine Practice?mentioning
confidence: 81%
“…177 However, one study found no difference in overall duration because, although the set-up time was significantly longer, this was balanced out by a significantly shorter operative time, which the authors argued was due to the technical advantages that the robot provides to the surgeon. 178 Given the high cost of purchasing and maintaining a robotic system, minimising additional costs associated with increased operation duration was perceived by some as essential for ensuring that RAS is integrated into routine practice. 147,179 Overall, there was broad agreement in the perception that operation duration decreases as experience increases, with this often being attributed to a decrease in set-up time.…”
Section: A Realist Review Of Stakeholders' Theoriesmentioning
confidence: 99%